Comparison of the dimensions design methodologies of the railway track bed structure according to frost effect in Slovakia and Lithuania - Ižvolt, Libor; Dobeš, Peter; Navikas, Deividas (Journal of Civil Engineering and Management, 2019)
This paper compares methods of designing the track bed structure that are used in the processes of design and review design of subgrade tracks located in Slovakia and Lithuania. Self-comparison is made on a particular type of track bed with the aim to highlight the differences between individual countries methodologies that affect not only the dimension of the sub-ballast layer, but also economic demands and reliability of the design of railways structure.